2021
DOI: 10.1186/s40643-021-00375-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing glucoamylase usage for commercial-scale ethanol production from starch using glucoamylase expressing Saccharomyces cerevisiae

Abstract: The development of yeast that converts raw corn or cassava starch to ethanol without adding the exogenous α-amylase and/or glucoamylase would reduce the overall ethanol production cost. In this study, two copies of codon-optimized Saccharomycopsis fibuligera glucoamylase genes were integrated into the genome of the industrial Saccharomyces cerevisiae strain CCTCC M94055, and the resulting strain CIBTS1522 showed comparable basic growth characters with the parental strain. We systemically evaluated the fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The ethanol content in culture medium is an important indicator of yeast metabolism. 38 As shown in Fig. 5, the high glucose group contained more ethanol in the culture medium, and the ethanol content of different groups demonstrated significant differences.…”
Section: Effect Of Glucose Levels On the Content Of Ethanol In Cultur...mentioning
confidence: 81%
See 1 more Smart Citation
“…The ethanol content in culture medium is an important indicator of yeast metabolism. 38 As shown in Fig. 5, the high glucose group contained more ethanol in the culture medium, and the ethanol content of different groups demonstrated significant differences.…”
Section: Effect Of Glucose Levels On the Content Of Ethanol In Cultur...mentioning
confidence: 81%
“…The ethanol content in culture medium is an important indicator of yeast metabolism 38 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glucoamylase can improve the fermentation rate and ethanol production, but it will increase the cost of ethanol production. To reduce the cost of ethanol production, the glucoamylase synthesis genes were integrated into industrial yeast by Wang et al (2021), and a recombinant strain CIBTS1522 was obtained, which can reduce the addition of glucoamylase by about 40%. The use of strains that can produce glucoamylase in the process of ethanol fermentation, which reduces the addition of glucoamylase and the cost of ethanol production effectiveness (Favaro et al, 2015; Kobayashi & Nakamura, 2004; Viswanathan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A synthetic gene for a tolerant glucoamylase was isolated from Aspergillus flavus NSH9 and expressed successfully in P. pastoris GS115 , and a recombinant glucoamylase strain (rGA2) was obtained by Kmr et al (2019). Based on the research of Favaro et al (2012), the optimizing glucoamylase synthetic genes were integrated into industrial S. cerevisiae by Wang et al (2021) and found that the recombinant strain could reduce the exogenous Saccharomyces adds by over 40% in actual ethanol production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation